Search
Ask a question
0

Simplify and show work for the equation

Simplify: . Show work
 
1/(x+2)-2/(x^2+5x+6)
 

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Adam S. | Professional and Proficient Math TutorProfessional and Proficient Math Tutor
0
1/(x + 2) - 2/(x^2+5x+6)
 
Use FOIL: x^2 + 5x + 6 = (x + 3)(x + 2)
 
1/(x + 2) - 2/((x + 3)(x + 2)))
 
multiply the first term by (x + 3)/(x + 3)
 
(x + 3)/((x + 3)(x + 2)) - 2/((x + 3)(x + 2)) = (x + 3 - 2)/((x + 3)(x + 2)) =
 
(x + 1)/((x + 3)(x + 2)) = (x + 1)/(x^2 + 5x + 6)
Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
(1/ (X+2) ) -  2 / ( X^2 + 5X +6) =
 
  1/ ( X+2 ) - 2/ ( X + 2) ( X +3 ) =
 
(  X +3 ) -2  / ( X +2)( X+3 )
 
    ( X +1 ) / ( X +2 ) ( X+3)